2022
DOI: 10.1097/wnr.0000000000001788
|View full text |Cite
|
Sign up to set email alerts
|

Loss of GBA in zebrafish leads to dopaminergic neurodegeneration, but overexpression of α-synuclein does not further worsen degeneration

Abstract: ObjectivesParkinson's disease is a neurodegenerative disorder that causes motor and nonmotor symptoms due to the loss of dopaminergic nerves and is characterized by the presence of Lewy bodies, which are mainly composed of α-synuclein. Glucosylceramidase beta (GBA), which is a causative gene of autosomal recessive Gaucher disease, is also known to be a risk gene for Parkinson's disease. In this study, we tried to detect synergistic effects of α-synuclein accumulation and gba depletion on dopaminergic neurodege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In zebrafish, one study found no presence of α‐synuclein aggregation nor DA neuron degeneration in a transgenic line expressing human α‐synuclein A53T (Kodera et al, 2022). Another study reported that transgenic lines expressing wild‐type and A53T human α‐synuclein exhibited a slight reduction of life span, an increase in apoptotic cell death, and impaired axonal mitochondrial transport (Lopez et al, 2022).…”
Section: Genetic Pd Models In Zebrafishmentioning
confidence: 99%
See 1 more Smart Citation
“…In zebrafish, one study found no presence of α‐synuclein aggregation nor DA neuron degeneration in a transgenic line expressing human α‐synuclein A53T (Kodera et al, 2022). Another study reported that transgenic lines expressing wild‐type and A53T human α‐synuclein exhibited a slight reduction of life span, an increase in apoptotic cell death, and impaired axonal mitochondrial transport (Lopez et al, 2022).…”
Section: Genetic Pd Models In Zebrafishmentioning
confidence: 99%
“…In zebrafish, Gba knockout resulted in DA neuron neurodegeneration. α‐Synuclein aggregation pathology was induced when these fish were crossed with human α‐synuclein A53T transgenic fish, but the level of neurodegeneration was not exacerbated (Kodera et al, 2022). Therefore, in zebrafish, the association between Gba deficiency and neurodegeneration may be α‐synuclein‐independent.…”
Section: Genetic Pd Models In Zebrafishmentioning
confidence: 99%